National Culture and Accounting Conservatism - Elbayoumi, Ahmed Fouad; Eljilany, Somya Mohamed; Hegazy, Ibrahim Raslan (STIE Malangkucecwara, 2024)
We test whether Hofstede (1980) cultural dimensions affect accounting conservatism in the banking sector. Our sample is 3593 banks-year observations from four countries. We find significant positive effect of uncertainty avoidance and power distance on accounting conservatism and a significant negative effect of individualism and masculinity on accounting conservatism. We robust our findings using cultural dimensions of House et al. (2004). We contribute to the literature as follows. First; we focus on the banking sector that has been marginalized by many researchers. Second; we cover the most recent period from 2013 to 2020. Third; we found new evidences of the significant relationships between the four dimensions of Hofstede (1980) and accounting conservatism in the banking sector. Fourth; the random effect method for panel data for regression is used in this study to control fixed years effect which enabled us to explain the role of culture in accounting conservatism.